The Actualization of Moderate Islamic Values In Madrasah - Syihabuddin, Muhammad Arif; Nafiuddin, Muhammad (Journal of Education and Religious Studies, 2023)
Madrasah, as an Islamic educational institution, plays a crucial role in shaping the moderate character of students. This research aimed to analyze the actualization of Islamic moderation values in madrasah. A qualitative method was employed for this research. Data were collected through observations, interviews, and document analysis. The findings indicated that the madrasahs endeavored to actualize Islamic moderation values through a curriculum that encompasses religious, ethical, and moral teachings of Islam. The actualization of moderate Islamic values was supported by extracurricular activities such as religious studies, seminars, and social events. The values of moderation being implemented include: 1) The value of tolerance (tasammuh); 2) Tajrid; 3) al-Tawasuth; 4) Al-Muwajahah; 5) Al-tawāzun; 6) Al-i’tidal; 7) Collaboration (musyarakah); 9) Harmony, promoting unity, integrity, and discipline; and 10) Al muhafadzatu a’la qodimi al sholeh wa al akhdzu bi jadidi al ashlah. However, this research also identified several challenges, such as limited resources and difficulties in understanding the life context of the students. In conclusion, the madrasah has significant potential to become an educational institution capable of producing a generation that lives and practices the values of moderate Islam in Indonesia.